Ностальгия в фильме Никиты Михалкова Урга: территория любви - Kaźmierczak, Natalia (Studia Rossica Posnaniensia, 2019)
The article is concerned with the interpretation of Nikita Mikhalkov’s artistic method as fiction phenomenology of nostalgia. Nostalgia is associated mainly with the reflective yearning for the past.